Duration-dependent physiological, perceptual, and technical changes during a 2-hour low-intensity training session in female cross-country skiers - Torvik, Per-Øyvind; Solli, Guro Strøm; Talsnes, Rune Kjøsen; Sandbakk, Øyvind (Frontiers in Physiology, 2025)
PurposeThis study investigated duration-dependent physiological, perceptual, and technical changes during a 2-hour low-intensity training (LIT) session in female cross-country (XC) skiers.MethodsTwelve national-level female XC skiers (age:21.4 ± 2.7 years, maximal oxygen uptake: 58.1 ± 5.3 mL min⁻1·kg⁻1) performed a 2-hour LIT session, roller-ski skating in the laboratory while alternating between two main sub-techniques (Gear-2 and Gear-3). Acute physiological and perceptual responses, including oxygen uptake, carbon dioxide production, ventilation, breathing frequency, respiratory exchange ratio, blood lactate concentration, and rate of perceived exertion, as well as kinematic variables (cycle length and cycle rate), were collected at four consecutive timepoints (T1–T4) for both sub-techniques. A post-session questionnaire collected data on perceived total, ventilatory, and mental exertion as well as perceived training quality.ResultsRelatively small duration-dependent changes were observed for most of the physiological measures. The most pronounced changes were a main effect of time on breathing frequency (BF; F (3,30) = 3.52, ηp2 = 0.260, P = 0.027) and rate of perceived exertion (RPE; F (3, 33) = 4.43, ηp2 = 0.287, P = 0.010). More specifically, BF was higher in Gear-3 at both T2 (45.5 ± 7.7 breaths·min-1) and T3 (45.5 ± 7.7), compared to T1 (43.2 ± 7.3, all P < 0.05). Furthermore, the rate of perceived exertion was higher in both Gear-2 and Gear-3 at T2 (G2: 12.1 ± 1.0, G3: 11.2 ± 1.6) and T3 (G2: 12.2 ± 1.1, G3: 11.2 ± 1.6), compared to T1 (G2: 11.5 ± 1.2, G3: 10.6 ± 1.2, all P < 0.05). No differences were observed in kinematic variables (cycle length and cycle rate) between T1 - T4. Lastly, no differences in perceived total, ventilatory, and mental exertion, as well as perceived training quality, were observed between the first and second half of the LIT session.ConclusionWell-trained female XC skiers performed a 2-hour LIT session while roller-ski skating in the laboratory with relatively small duration-dependent physiological, perceptual, and technical changes.